The synthesis of hydrogel from selective natural resource in Malaysia: a review - Shahira Sherliyani Kamal; Sabrina Soloi; Muhammad Irfan Hakim (Universiti Malaysia Sabah, 2024)
Hydrogels are hydrophilic polymer materials characterized by three-dimensional (3D) network structures that can absorb and retain significant amounts of water within their interstitial spaces. Due to their potential applications in advanced technologies across various sectors, including biomedical, pharmaceutical, biotechnology, bioseparation, biosensor, livestock, oil recovery, and cosmetics industries, hydrogels—often referred to as smart or hungry networks— are the subject of extensive scientific research. Recently, researchers have focused on creating hydrogels from natural resources to promote environmentally sustainable technologies. This review provides a concise overview of the use of oil palm empty fruit bunch (OPEFB) cellulose, C. asiatica asiaticoside, and cross-linked honey, sourced from Malaysia, in the development of hydrogels.